Strobilanthes hongii, a new species of Acanthaceae from Guizhou, China - Chen, Fenglin; Deng, Yunfei; Xiong, Zhibin; Ran, Jingcheng (Phytotaxa, 2019)
Strobilanthes hongii, a new species of Acanthaceae is described and illustrated from Libo, Guizhou, China. The new species is similar to S. pateriformis and S. truncata, but differs by the characters of leaf blade, bracteole and calyx and pollen grains. The new species is plietesial and grows in forest on limestone hills. The conservation status of S. hongii is assessed as “Vulnerable (VU)” according to the IUCN red list categories and criteria.